2015
DOI: 10.1177/1363461515571626
|View full text |Cite
|
Sign up to set email alerts
|

‘A thing full of stories’: Traditional healers’ explanations of epilepsy and perspectives on collaboration with biomedical health care in Cape Town

Abstract: The experience of epilepsy is profoundly culturally mediated and the meanings attributed to the condition can have a great impact on its social course. This qualitative study used Kleinman’s Explanatory Model framework to explore traditional healers’ perspectives on epilepsy in an urban township in Cape Town, South Africa. The healers who participated in the study were Xhosa-speaking, had experience caring for patients with epilepsy, and had not received any training on epilepsy. Six individual in-depth interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 60 publications
5
57
1
Order By: Relevance
“…The use of plant and animal material in seizure treatment is never standardized and is often adjusted and applied depending on the person's needs and the perceived cause of the seizures. This corresponds to findings from studies performed in other African countries that reported the use of herbs, animal products, and insects during treatment . Success is measured by the complete absence of seizures, which is again entirely possible if the THP is treating the person for what is known as PNES according to Western definitions.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The use of plant and animal material in seizure treatment is never standardized and is often adjusted and applied depending on the person's needs and the perceived cause of the seizures. This corresponds to findings from studies performed in other African countries that reported the use of herbs, animal products, and insects during treatment . Success is measured by the complete absence of seizures, which is again entirely possible if the THP is treating the person for what is known as PNES according to Western definitions.…”
Section: Discussionsupporting
confidence: 79%
“…They do, however, make a distinction between medical seizures, which can be treated by Western medicine, and spiritual seizures that can be treated only by THPs. A study among healers in South Africa reported similar findings where participants provided diverse biomedical and local cultural explanations as to the causes of epilepsy . A distinction is therefore made between seizures as a result of identifiable physical causes and seizures that originate as a result of psychological or spiritual causes.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations